From the Manuscripts of 44 towards a historical conception of alienation in the Grundrisse (1857-1858) - Romero, Antonio (2023)
(Romero, 2021). The years from 1845 to 1853 are considered as part of a transition period in Marx’s thought, that is, between the Manuscripts of 1844 and the Grundrisse (Drafts) of 1857-1858. In this context, the genetic relationship between the manuscripts and the drafts is examined, using the category of alienated work as a guiding thread, already purged by Marx of all metaphysical vestiges. As will be shown later, this category was not abandoned by Marx at the crucial moments, when he decided to convert the “Draft Project of 1859”, a continuation of the Contribution (the missing “Capital Chapter”), into the new project of “critique of political economy” (1862). The article ends by offering some final thoughts.